Amphiphilic triblock copolymer as well as preparation method and application thereof
By designing amphiphilic triblock copolymers and combining poly(2-methyloxazoline) and poly(lactic acid), the problem of poor bioaffinity of existing amphiphilic block copolymers is solved, and high film formation rate, low film drop rate and good bioaffinity are achieved, and it is suitable for nanopore sequencing and other applications.
Patent Information
- Application Number
- CN202510224228.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-11
AI Technical Summary
The existing amphiphilic block copolymers have poor bioaffinity when forming membranes, requiring higher intensity of external stimulation and a larger amount of nanopore protein, resulting in limited application scenarios.
An amphiphilic triblock copolymer is designed, and its structure includes hydrophilic block A, hydrophobic block B and hydrophilic block A, specifically a combination of poly(2-methyloxazoline) and poly(lactic acid). By controlling the degree of polymerization and proportion of the blocks, the interaction between polymer block structural units is regulated to ensure the rheological characteristics of polylactic acid.
It has achieved high film formation rate, low film drop rate and good bioaffinity. The stability of the bionic film is even higher than that of the bionic film formed by polysiloxane copolymers, and is suitable for application scenarios such as nanopore sequencing.
Smart Images

Figure CN119798654A_ABST
Abstract
Description
[0001] This application is a divisional application based on the Chinese invention patent application with application number 202411815397.X, application date December 11, 2024, and invention name "A kind of amphiphilic triblock copolymer and its preparation method and application". Technical Field
[0002] The invention relates to the field of polymer materials, and in particular to an amphiphilic triblock copolymer and a preparation method and application thereof. Background Art
[0003] Existing membrane-forming technologies mainly use the self-assembly properties of phospholipid molecules or amphiphilic block copolymers at the water-oil interface to form amphiphilic molecular membranes. Phospholipid molecules are natural amphiphilic molecules with a hydrophilic nitrogen or phosphorus head at one end and a hydrophobic (lipophilic) long hydrocarbon chain at the other end. When arranged, the hydrophilic ends are close to each other and the hydrophobic ends are close to each other to form a phospholipid bilayer structure. Since the phospholipid bilayer (referred to as phospholipid membrane) formed by phospholipids has a natural affinity with biological molecules, has a good affinity with a variety of channel proteins (referred to as nanopore proteins) and has a high embedding efficiency of nanopore proteins, phospholipid membranes are often used in the field of nanopore sequencing to simulate cell membrane structures and carry nanopore proteins for sequencing. However, due to the weak mechanical strength of phospholipid molecules, phospholipid membranes have defects such as poor stability. Although this can meet the needs of most biological, physical and physiological experiments, it is far from enough for the technical application of channel proteins.
[0004] The existing polymers used to form biomimetic membranes are amphiphilic block copolymers (such as polysiloxane copolymers PMOXA-PDMS-PMOXA), whose intermolecular forces are stronger than those of phospholipid molecules, and the molecular stacking density is large, so the formed polymer membrane has high mechanical strength and stability. However, the existing amphiphilic block copolymers have disadvantages such as low bioaffinity and film-forming performance, which are specifically reflected in the fact that when embedding holes, they must be combined with high-intensity external stimuli (such as high-intensity voltage stimulation) and require the use of a large amount of nanoporous proteins. In order to improve the bioaffinity of polymer membranes, WO2023123434A1 discloses a phospholipid / polymer biomimetic composite formula membrane and its preparation method and application, which adopts a biomimetic composite formula membrane containing polymer molecules and phospholipid molecules to enhance the bioaffinity of polysiloxane copolymer biomimetic membranes, but its operation is complicated and still requires the use of a large amount of nanoporous proteins, so the application scenarios are relatively limited. Summary of the invention
[0005] In a first aspect, the present invention provides an amphiphilic triblock copolymer, characterized in that the amphiphilic triblock copolymer has a hydrophilic block A-hydrophobic block B-hydrophilic block A structure, wherein the structural unit of the hydrophilic block A includes poly(2-methyloxazoline), the structural unit of the hydrophobic block B includes poly(lactic acid), the degree of polymerization of the hydrophilic block A is n, the degree of polymerization of the hydrophobic block B is m, and m+n≤25; the ratio of the total degree of polymerization of the hydrophilic block A to the total degree of polymerization of the amphiphilic triblock copolymer includes 20%-40%, and the number average molecular weight of the amphiphilic triblock copolymer includes 2000-6000 g / mol.
[0006] As used herein, "degree of polymerization" refers to the number of repeating structural units of the polymer blocks (e.g., hydrophilic blocks, hydrophobic blocks) of the amphiphilic triblock copolymer. In some embodiments, the amphiphilic triblock copolymer has a hydrophilic block A-hydrophobic block B-hydrophilic block A structure. In some embodiments, the amphiphilic triblock copolymer has PMOXA n -PLA m -PMOXA n Structure, wherein m represents the degree of polymerization of the hydrophobic block B, n represents the degree of polymerization of the hydrophilic block A, the total degree of polymerization of the hydrophilic block A is 2n, and the total degree of polymerization of the amphiphilic triblock copolymer is 2n+m. In some embodiments, m and n are both integers. In some embodiments, m is an integer ≥1, and n is an integer ≥1. In some embodiments, the degree of polymerization of the hydrophilic block A ranges from about 1 to about 5. In some embodiments, the degree of polymerization of the hydrophobic block B ranges from about 1 to about 20.
[0007] In some embodiments, m+n≤20.
[0008] In some embodiments, n / m comprises 1:3-8.
[0009] In some embodiments, n / m includes (1-2): (6-7).
[0010] In some embodiments, the amphiphilic triblock copolymer is HO-PMOXA n -PLA m -PMOXA n -OH, where m and n represent the degree of polymerization.
[0011] In some embodiments, n is 2 or 3 or 4.
[0012] In some embodiments, m is 12 or 13 or 14.
[0013] In some embodiments, the amphiphilic triblock copolymer is HO-PMOXA4-PLA 13-PMOXA4-OH.
[0014] In some embodiments, the amphiphilic triblock copolymer is HO-PMOXA2-PLA 13 -PMOXA2-OH.
[0015] In some embodiments, the amphiphilic triblock copolymer is MA-PMOXA n -PLA m -PMOXA n -MA, where m and n represent the degree of polymerization.
[0016] In some embodiments, n is 2 or 3 or 4.
[0017] In some embodiments, m is 12 or 13 or 14.
[0018] In some embodiments, the amphiphilic triblock copolymer is MA-PMOXA4-PLA 13 -PMOXA4-MA.
[0019] In some embodiments, the amphiphilic triblock copolymer is MA-PMOXA2-PLA 13 -PMOXA2-MA.
[0020] In a second aspect, the present invention also provides the use of the above-mentioned amphiphilic triblock copolymer in the preparation of a biomimetic membrane.
[0021] In some embodiments, the biomimetic membrane is used to embed nanopore proteins.
[0022] In some embodiments, the application comprises nanopore sequencing.
[0023] In some embodiments, the embedding method includes adding a nanopore protein solution to the biomimetic membrane and then applying an embedding voltage to embed the nanopore protein.
[0024] In some embodiments, the final concentration of the nanoporous protein solution at the biomimetic membrane of a single microporous structure is 1-2×10 -6 mg / mL.
[0025] In some embodiments, the volume of the nanoporous protein solution added to the biomimetic membrane of a single microporous structure comprises 1-5×10 -3 μL.
[0026] In some embodiments, the embedding voltage comprises 300-400 mV.
[0027] In some embodiments, the membrane capacitance of the biomimetic membrane is 15-40 pF.
[0028] In some embodiments, the biomimetic membrane is prepared by the following method: S301 preparing an amphiphilic triblock copolymer solution; In some embodiments, the solvent of the amphiphilic triblock copolymer solution includes one or more of silicone oil, methylphenyl silicone oil, n-hexane, PDMS, decane, and hexadecane.
[0029] In some embodiments, the mass concentration of the amphiphilic triblock copolymer in the amphiphilic triblock copolymer solution is 10-20 mg / mL.
[0030] S302 preparing a polar solution; In some embodiments, the polar solution includes a phosphate buffer solution, a HEPES buffer solution containing KCl or NaCl, a CAPS buffer solution containing KCl or NaCl, or a CAPS buffer solution containing H3PO4, K2[Fe(CN)6], or K3[Fe(CN)6].
[0031] S303 adding the polar solution to the pretreated nanopore sequencing chip; S304 After adding the amphiphilic triblock copolymer solution to the microporous structure of the nanopore sequencing chip, the polar solution is added, and the amphiphilic triblock copolymer self-assembles into the bionic membrane at the microporous structure.
[0032] In some embodiments, the nanopore sequencing chip generally has ≥2 micropore structures. In some embodiments, the nanopore sequencing chip has 256 micropore structures.
[0033] In some embodiments, the final concentration of the nanoporous protein solution at the biomimetic membrane of a single microporous structure is 1-2×10 -6 mg / mL.
[0034] In some embodiments, the volume of the nanoporous protein solution added to the biomimetic membrane of a single microporous structure comprises 1-5×10 -3 μL.
[0035] In some embodiments, the total volume of nanopore protein solution added comprises 0.6-0.8 μL.
[0036] In some embodiments, the embedding voltage comprises 300-400 mV.
[0037] In some embodiments, the membrane capacitance of the biomimetic membrane is 15-40 pF.
[0038] In a third aspect, the present invention further provides a method for preparing the above-mentioned amphiphilic triblock copolymer, characterized in that the preparation method comprises the following steps: S101 adding ethylene glycol, lactide and a first catalyst into a reaction container to obtain a first mixture; In some embodiments, the reaction vessel comprises a pressure-resistant sealing tube.
[0039] In some embodiments, the molar ratio of the ethylene glycol to the lactide (feed ratio, the same below) is 1:15-40.
[0040] S102 reacting the first mixture in an oil bath at a first temperature for a first time to obtain a first product; In some embodiments, the first time comprises 15-20 hours.
[0041] In some embodiments, the first temperature comprises 100-110°C.
[0042] In some embodiments, the first catalyst comprises stannous octoate.
[0043] S103 mixing the first product, pyridine and trifluoromethanesulfonic anhydride and reacting for a second time to obtain a second product; In some embodiments, the molar ratio of the first product to the trifluoromethanesulfonic anhydride comprises 1:5-10.
[0044] In some embodiments, the second time comprises 0.25-1 hour.
[0045] S104 mixing the second product and 2-methyl-2-oxazoline and reacting for a third time to obtain a third product; In some embodiments, the third time comprises 0.25-1 hour.
[0046] S105 adding triethylamine to the third product and reacting for a fourth time to obtain a fourth product; In some embodiments, the fourth time comprises 0.5-2 hours.
[0047] In some embodiments, the molar ratio of the second product to the triethylamine comprises 1:2-5.
[0048] In some embodiments, the molar ratio of the second product to the 2-methyl-2-oxazoline comprises 1:4-15.
[0049] In some embodiments, the method further includes S106 mixing and reacting the fourth product with isocyanoethyl methacrylate to obtain a fifth product.
[0050] Compared with the prior art, the beneficial effects of the present invention include at least the following aspects: Due to the strong intermolecular interaction of amphiphilic block copolymers, polymer membranes are superior to phospholipid membranes in terms of stability. However, their bioaffinity is relatively poor, which is not only reflected in the low film-forming rate, but also in the fact that the embedded pores must be accompanied by high-intensity external stimuli and require the use of a large amount of nanopore proteins.
[0051] Polylactic acid is a biodegradable polyester polymer, that is, each structural unit on the molecular chain of this type of polymer is connected by an ester bond that is easily hydrolyzed. Therefore, the existing technology often applies polylactic acid to fields such as sustained release, using its biodegradability to release molecules such as proteins. In addition, it is reported that when the molecular weight of polylactic acid is less than 3000, the mechanical properties are poor and the practical value is not high; only when the relative molecular weight of polylactic acid is greater than 6000, it will have better physical and mechanical properties.
[0052] The present invention provides an amphiphilic triblock copolymer, that is, a poly(lactic acid) as the middle hydrophobic block B and poly(2-methyloxazoline) as the hydrophilic blocks A on both sides of the structure PMOXA n -PLA m -PMOXA n The present invention precisely regulates the interaction mode between the polymer block structural units and ensures the rheological properties of the polylactic acid in the amphiphilic triblock copolymer (such as degradation rate, impact strength, hydrophilicity and hydrophobicity, thermal stability, etc.) by controlling the degree of polymerization and ratio of the polymer blocks. The results show that the amphiphilic triblock copolymer provided by the present invention not only has a high film-forming rate, but also has an extremely low film-falling rate, and the film-falling rate on the 60th day can be controlled at about 2.5%. In other words, the amphiphilic triblock copolymer provided by the present invention can not only successfully self-assemble to form a bionic membrane, but also will not degrade in the long-term buffer and voltage stimulation environment, and will not release nanoporous proteins. The stability is even higher than the bionic membrane formed by the polysiloxane copolymer with better stability, which is recognized.
[0053] It should be noted that the chemical properties of the amphiphilic triblock copolymer and the biomimetic membrane formed by it affect the embedding of the nanoporous protein, and the combination of the biological entity and the biomimetic membrane requires more stringent conditions. The present invention controls the degree of polymerization and its ratio of the polymer block (such as the total degree of polymerization of the hydrophilic block, the ratio of the degree of polymerization of the hydrophilic block and the hydrophobic block) and the number average molecular weight at a suitable level, which not only ensures a high film formation rate, but also ensures a good membrane-protein interaction, that is, the amphiphilic triblock copolymer provided by the present invention can be adapted to different nanoporous proteins and the nanoporous protein can be stably present on the biomimetic membrane formed by it for a long time (for example, more than 60 days), and the bioaffinity is very close to the phospholipid membrane, and the amount of biological protein required to form a biomimetic membrane is less than that of the polysiloxane copolymer, and the embedding voltage is lower. Compared with the biomimetic membrane formed by polysiloxane copolymers, the amphiphilic triblock copolymer synthesized in the present invention has excellent bioaffinity, membrane pore matching and easy-to-achieve embedding conditions. The embedding voltage stimulation and protein amount required are low, which not only saves experimental costs, but also avoids to a certain extent the problems of conformational instability or membrane rupture of nanopore proteins caused by the stimulation of higher embedding voltage.
[0054] In summary, the bionic membrane formed by the amphiphilic triblock copolymer provided by the present invention combines the advantages of phospholipid membrane and polysiloxane copolymer bionic membrane, that is, while maintaining the characteristics of strong stability of the polysiloxane copolymer bionic membrane, the film formation rate, bioaffinity and membrane pore matching are very close to those of the phospholipid membrane, and the current problems of poor stability and difficulty in storage of the phospholipid membrane will not occur. It is suitable for application scenarios such as nanopore sequencing. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual scale. Obviously, the drawings described below are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without paying creative labor.
[0056] Figure 1 The synthetic route of polylactic acid triblock copolymer HO-PMOXA-PLA-PMOXA-OH; Figure 2 This is the result of H NMR spectrum of the dihydroxy-terminated polylactic acid product PLA; Figure 3 It is a polylactic acid triblock copolymer (HO-PMOXA4-PLA 13 -PMOXA4-OH) H NMR spectrum results; Figure 4 It is a polylactic acid triblock copolymer (HO-PMOXA4-PLA 13 -PMOXA4-OH) membrane capacitance electrical characterization results (first day of film formation); Figure 5 It is a polylactic acid triblock copolymer (MA-PMOXA4-PLA 13 -PMOXA4-MA) membrane capacitance electrical characterization results (first day of membrane formation); Figure 6 It is a polylactic acid triblock copolymer (HO-PMOXA2-PLA 13 -PMOXA2-OH) membrane capacitance electrical characterization results (first day of film formation); Figure 7 It is a polylactic acid triblock copolymer (HO-PMOXA4-PLA 13 -PMOXA4-OH) membrane capacitance electrical characterization results (60 days after film formation); Figure 8 For polysiloxane copolymer (HO-PMOXA6-PDMS 27 -PMOXA6-OH) membrane capacitance electrical characterization results (60 days after film formation); Fig. 9 The result of the biomimetic membrane formed by polylactic acid triblock copolymer being embedded in single-hole nanoporin; Fig.10 The result of the biomimetic membrane formed by polylactic acid triblock copolymer being embedded in porous nanoporous protein; Fig.11 This is the membrane current signal result after embedding nanopore protein. DETAILED DESCRIPTION
[0057] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0058] Herein, suffixes such as "module", "component" or "unit" used to represent elements are only used to facilitate the description of the present invention, and have no specific meanings by themselves. Therefore, "module", "component" or "unit" can be used mixedly.
[0059] In this document, the directions or positional relationships indicated by the terms "upper", "lower", "inner", "outer", "front", "rear", "one end", "the other end", etc. are based on the directions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the devices or elements referred to must have a specific direction, be constructed and operate in a specific direction, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.
[0060] Herein "and / or" includes any and all combinations of one or more of the associated listed items.
[0061] Herein, "plurality" means two or more than two, ie, it includes two, three, four, five, etc.
[0062] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0063] As used in this specification, the term "about" typically means + / - 5% of the stated value, more typically + / - 4% of the stated value, more typically + / - 3% of the stated value, more typically + / - 2% of the stated value, even more typically + / - 1% of the stated value, and even more typically + / - 0.5% of the stated value.
[0064] In this specification, some embodiments may be disclosed in a format of being in a range. It should be understood that this description of "being in a range" is only for convenience and brevity, and should not be interpreted as a rigid limitation on the disclosed range. Therefore, the description of the range should be considered to have specifically disclosed all possible sub-ranges and independent numerical values within this range. For example, the description of the range 1-6 should be considered to have specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as individual numbers within this range, such as 1, 2, 3, 4, 5 and 6. Regardless of the breadth of the range, the above rules apply.
[0065] Embodiment 1 Triblock copolymer 1 (HO-PMOXA4-PLA 13 Synthesis of 2-PMOXA4-OH) The synthetic route of polylactic acid triblock copolymer HO-PMOXA-PLA-PMOXA-OH is shown in Figure 1 .
[0066] 1.1 Synthesis of dihydroxy-terminated polylactic acid product PLA A pressure-resistant sealed tube was selected as the reaction bottle, and raw materials ethylene glycol (2.0 mmol, 0.124 g) and lactide (L-LA, 31.2 mmol, 4.496 g) were added to the pressure-resistant sealed tube. Stannous octoate (Sn(Oct)2, 7.5 ml, 0.15 mg / ml) was dissolved in dichloromethane and added to the reaction system, and then the dichloromethane was removed by vortexing under reduced pressure. After the pressure-resistant sealed tube was sealed, it was placed in a 105°C oil bath for reaction for 16 hours; it was cooled to room temperature to obtain a dihydroxy-terminated polylactic acid product PLA. The part of the pressure-resistant sealed tube containing the raw materials can be completely immersed in the oil bath, the raw materials can be fully reacted, and the obtained product is highly pure, and subsequent reactions can be carried out without purification. The sample was sent for NMR testing using a deuterated reagent as the solvent. The nuclear magnetic hydrogen spectrum of the dihydroxy-terminated polylactic acid product PLA is shown in Figure 2 . 1 The H-NMR test results showed the presence of the characteristic peaks of the dihydroxy-terminated polylactic acid product PLA, confirming that the target product had been obtained and could proceed to the next step of reaction.
[0067] If a conventional double-necked round-bottom flask is used as the reaction flask, the starting raw materials will be melted and then cooled and gathered at the bottleneck of the upper part of the reaction flask, which will hinder the reaction and terminate the reaction, making it difficult to obtain the target polylactic acid product PLA.
[0068] 1.2 Synthesis of double-terminal trifluoromethanesulfonate functionalized PLA Take the dihydroxy-terminated polylactic acid product PLA (1.5 mmol, 2.92 g) obtained in step 1.1 and dissolve it in 30 ml of n-hexane. Place the reaction bottle in a low-temperature constant temperature reaction domain and cool it to 0°C. After adding (10.75 mmol, 0.85 g) of pyridine, add trifluoromethanesulfonic anhydride ((CF3SO2)2O, 10.38 mmol, 2.93 g) dropwise under stirring, and react at room temperature for 0.5 h. After adding 10 ml of chloroform, filter under reduced pressure, and remove the solvent from the obtained filtrate under reduced pressure to obtain the functionalized product of difluoromethanesulfonated PLA.
[0069] 1.3 Synthesis of triblock copolymer 1 Take the double-terminal trifluoromethanesulfonate functionalized product of PLA (1.0 mmol, 2.20 g) obtained in step 1.2, add 15 ml of 1,2-dichloroethane to dissolve, add 2-methyl-2-oxazoline (9.6 mmol, 0.82 g), stir at room temperature for 0.5 h, heat to 40 ° C in an oil bath and react for 48 h. After the reaction is completed, cool to room temperature, add organic base triethylamine (Et3N, 2.075 mmol, 288 μL), stir at room temperature for 1 h, spin off the solvent and purify the product to obtain the hydroxyl-terminated triblock copolymer HO-PMOXA4-PLA 13 -PMOXA4-OH. The number average molecular weight of the synthesized polylactic acid triblock copolymer 1 is about 2600 g / mol. The sample was sent for NMR test using deuterated reagent as solvent. HO-PMOXA4-PLA 13 -PMOXA4-OH H NMR spectrum is shown in Figure 3 . 1 The H-NMR test results showed the presence of the characteristic peak of polylactic acid triblock copolymer 1. After confirming that the target product had been obtained, the film formation and pore embedding experiments on the nanopore sequencing chip were continued.
[0070] This example also tests other bases (inorganic bases such as potassium hydroxide and sodium carbonate, and organic bases such as 4-dimethylaminopyridine). Since PLA has a polyester skeleton structure, the addition of other bases is prone to alkaline hydrolysis, resulting in chain scission and decomposition. The hydrolysis reaction under the catalysis of triethylamine has the best effect, so triethylamine is selected for preparation.
[0071] Embodiment 2 Triblock copolymer 2 (HO-PMOXA2-PLA 13 Synthesis of 2-PMOXA2-OH) The difference between this embodiment and the first embodiment lies in the different polymerization degrees and ratios of the hydrophilic block and the hydrophobic block.
[0072] 2.1 Synthesis of dihydroxy-terminated polylactic acid product PLA Add raw materials ethylene glycol (2.0 mmol, 0.124 g) and lactide (31.2 mmol, 4.496 g) to the pressure-resistant sealed tube, dissolve stannous octoate (7.5 ml, 0.15 mg / ml) in dichloromethane and add it to the reaction system, then remove the dichloromethane under reduced pressure. After sealing the pressure-resistant sealed tube, place it in an oil bath at 105°C for 16 h; cool it to room temperature to obtain the dihydroxy-terminated polylactic acid product PLA.
[0073] 2.2 Synthesis of double-terminal trifluoromethanesulfonate functionalized PLA Take the dihydroxy-terminated polylactic acid product PLA (1.5 mmol, 2.92 g) obtained in step 2.1 and dissolve it in 30 ml of n-hexane. Place the reaction bottle in a low-temperature constant temperature reaction domain and lower it to 0°C. After adding (10.75 mmol, 0.85 g) of pyridine, add trifluoromethanesulfonic anhydride (10.38 mmol, 2.93 g) dropwise under stirring, and react at room temperature for 0.5 h. After adding 10 ml of chloroform, filter under reduced pressure, and remove the solvent from the obtained filtrate under reduced pressure to obtain the functionalized product of PLA with double-terminal trifluoromethanesulfonate ester.
[0074] 2.3 Synthesis of triblock copolymer 2 Take the double-terminal trifluoromethanesulfonate functionalized product of PLA in step 2.2 (1.0 mmol, 2.20 g), add 15 ml 1,2-dichloroethane to dissolve, add 2-methyl-2-oxazoline (4.8 mmol, 0.41 g), stir at room temperature for 0.5 h, heat the oil bath to 40 ° C and react for 48 h. After the reaction is completed, cool to room temperature, add organic base triethylamine (2.075 mmol, 288 μL), stir at room temperature for 1 h, spin off the solvent and purify the product to obtain the hydroxyl-terminated triblock copolymer HO-PMOXA2-PLA 13 -PMOXA2-OH. After confirming that the target product has been obtained, the film formation and pore embedding experiments on the nanopore sequencing chip are continued. The number average molecular weight of the synthesized triblock copolymer 2 is about 2290 g / mol.
[0075] Embodiment 3 Triblock copolymer 3 (HO-PMOXA6-PLA 26 Synthesis of 2-PMOXA6-OH) The difference between this embodiment and the first embodiment lies in the different polymerization degrees and ratios of the hydrophilic block and the hydrophobic block.
[0076] 3.1 Synthesis of dihydroxy-terminated polylactic acid product PLA Add raw materials ethylene glycol (2.0 mmol, 0.124 g) and lactide (62.4 mmol, 8.992 g) to the pressure-resistant sealed tube, dissolve stannous octoate (15 ml, 0.30 mg / ml) in dichloromethane and add it to the reaction system, then remove the dichloromethane under reduced pressure. After sealing the pressure-resistant sealed tube, place it in an oil bath at 105°C for 16 h; cool it to room temperature to obtain the dihydroxy-terminated polylactic acid product PLA.
[0077] 3.2 Synthesis of double-terminal trifluoromethanesulfonate functionalized PLA Take the dihydroxy-terminated polylactic acid product PLA (1.5 mmol, 5.754 g) obtained in step 3.1 and dissolve it in 30 ml of n-hexane. Place the reaction bottle in a low-temperature constant temperature reaction domain and lower it to 0°C. After adding (10.75 mmol, 0.85 g) of pyridine, add trifluoromethanesulfonic anhydride (10.38 mmol, 2.93 g) dropwise under stirring, and react at room temperature for 0.5 h. After adding 10 ml of chloroform, filter under reduced pressure, and remove the solvent from the obtained filtrate under reduced pressure to obtain the functionalized product of difluoromethanesulfonated PLA.
[0078] 3.3 Synthesis of triblock copolymer 3 Take the double-terminal trifluoromethanesulfonate functionalized product of PLA in step 3.2 (1.0 mmol, 3.83 g), add 15 ml 1,2-dichloroethane to dissolve, add 2-methyl-2-oxazoline (14.4 mmol, 1.23 g), stir at room temperature for 0.5 h, heat the oil bath to 40 ° C and react for 48 h. After the reaction is completed, cool to room temperature, add organic base triethylamine (2.075 mmol, 288 μL), stir at room temperature for 1 h, spin off the solvent and purify the product to obtain the hydroxyl-terminated triblock copolymer HO-PMOXA6-PLA 26 -PMOXA6-OH. After confirming that the target product has been obtained, the film formation and pore embedding experiments on the nanopore sequencing chip are continued. The number average molecular weight of the generated triblock copolymer 3 is about 4860 g / mol.
[0079] Embodiment 4 Triblock copolymer 4 (MA-PMOXA4-PLA 13 Synthesis of 2-PMOXA4-MA The difference between this embodiment and the first embodiment is that the end capping groups of the triblock copolymer are different. The first embodiment is hydroxyl end capping, and the present embodiment is double bond ester end capping. The triblock copolymer 4 can be used for UV crosslinking and curing, so that the triblock copolymer is more stable in forming a biomimetic film on the nanopore sequencing chip. The specific preparation method is as follows: At room temperature, 2.14 g HO-PMOXA4-PLA was added to a three-necked round-bottom flask. 13 -PMOXA4-OH and 10 mL of dry chloroform were completely dissolved into a milky white viscous liquid after nearly 2 hours. 210 mg of isocyanoethyl methacrylate (IEM) and 20 mg of dibutyltin dilaurate were added to the solution. The solution was stirred and reacted for 48 hours under light-proof conditions. After the reaction, the solvent was removed under high vacuum at 0°C to obtain a crude product. The crude product was ultrafiltered in a water / ethanol mixture to remove small molecular weight impurities to obtain a relatively pure colorless solid triblock copolymer 4 (MA-PMOXA4-PLA 13-PMOXA4-MA). After confirming that the target product has been obtained, the film formation and pore embedding experiments on the nanopore sequencing chip are continued. MA indicates that the end-capping group of the triblock copolymer is a methacrylate group.
[0080] The test results of the total polymerization degree ratio of the hydrophilic block of the polylactic acid triblock polymer prepared in Examples 1 to 4 (i.e., the ratio of the total polymerization degree of the hydrophilic block to the total polymerization degree of the polylactic acid triblock polymer) and the number average molecular weight are shown in Table 1 below.
[0081] Table 1 Test Example 1 Film formation on nanopore sequencing chips A method for preparing a phospholipid membrane on a nanopore sequencing chip comprises the following steps: S201: preparing a non-polar phospholipid solution, wherein the non-polar phospholipid solution may be a solution of silicone oil, methylphenyl silicone oil, n-hexane, PDMS, decane or hexadecane containing phospholipids, wherein the phospholipids may be glycerophospholipids or sphingomyelin, and the glycerophospholipids may be one or more of phosphatidic acid, phosphatidylcholine, phosphatidylethanolamine, phosphatidylinositol and phosphatidylglycerol. The mass concentration of the phospholipids in the non-polar phospholipid solution is 10-20 mg / mL.
[0082] S202: preparing a polar solution, wherein the polar solution may be a phosphate buffer solution, a HEPES buffer solution containing KCl or NaCl, a CAPS buffer solution containing KCl or NaCl, or a CAPS buffer solution containing H3PO4, K2[Fe(CN)6], or K3[Fe(CN)6].
[0083] S203 adding the polar solution to the pretreated nanopore sequencing chip.
[0084] S204 After adding the non-polar phospholipid solution to the nanopore sequencing chip, a polar solution is added, that is, a polar-non-polar-polar system is formed in the functional structure area of the nanopore sequencing chip, which self-assembles into a phospholipid membrane, and the membrane formation process is completed.
[0085] The core principle of sequencing in a nanopore sequencing device is to fix a nanopore protein on an amphiphilic molecular membrane, then unwind the double-stranded DNA into a single strand, and use the motor protein to pull the single-stranded DNA through the nanopore. Different bases in a single strand of DNA have different chemical structures and carry different charges. When passing through the nanopore, they will cause changes in the current on the amphiphilic molecular membrane and generate electrical signals, that is, the bases are identified by capturing the changes in the current. Therefore, the stability of the amphiphilic molecular membrane is very important for nanopore sequencing.
[0086] The film-forming effect can be detected by electrical characterization of membrane capacitance. The thickness of the membrane formed in each micropore of the nanopore sequencing chip can be determined by measuring its capacitance. The thickness of the phospholipid membrane formed is different, and the electrical characterization will also be different. In the electrical characterization diagram after film formation, there are 256 rectangular blocks, that is, the number of membrane capacitances that can be measured each time is 256. Each rectangular block represents a membrane capacitor corresponding to a micropore structure, and the value in the rectangular block represents the capacitance value of the membrane capacitor.
[0087] The color depth of each rectangular electrical representation is related to the size of the membrane capacitance value. The capacitance value can represent the state of different micropores, such as whether a membrane is formed and the thickness of the membrane layer. Specifically, for phospholipid membranes, a capacitance value of 25-30 pF is displayed as gray-green, indicating that a phospholipid membrane with too large a thickness is formed; a capacitance value in the range of 30-50 pF is displayed as light green, indicating that a phospholipid membrane with appropriate thickness is formed; a capacitance value below 25 pF or above 50 pF is displayed as red, indicating that an unqualified membrane is formed.
[0088] The membrane capacitance of phospholipids in nanopore sequencing chips is generally 25-50 pF.
[0089] A method for preparing a biomimetic membrane on a nanopore sequencing chip comprises the following steps: S301: preparing a nonpolar amphiphilic block copolymer solution, wherein the nonpolar amphiphilic block copolymer solution may be a solution of silicone oil, methylphenyl silicone oil, n-hexane, PDMS, decane or hexadecane containing an amphiphilic triblock polymer, wherein the mass concentration of the amphiphilic block copolymer in the nonpolar amphiphilic block copolymer solution is 10-20 mg / mL.
[0090] S302: Prepare a polar solution, which may be a phosphate buffer solution, a HEPES buffer solution containing KCl or NaCl, a CAPS buffer solution containing KCl or NaCl, or a CAPS buffer solution containing H3PO4, K2[Fe(CN)6], or K3[Fe(CN)6].
[0091] S303 adding the polar solution to the pretreated nanopore sequencing chip.
[0092] S304 After adding the non-polar amphiphilic block copolymer solution to the nanopore sequencing chip, a polar solution is added, that is, a polar-non-polar-polar system is formed in the functional structure area of the nanopore sequencing chip, which is self-assembled into a bionic membrane (which can also be understood as a polymer membrane), and the membrane formation process is completed.
[0093] Specifically, for the bionic membrane, a capacitance value of 15-20 pF is displayed as gray-green, indicating that a bionic membrane with too large a thickness is formed; a capacitance value in the range of 20-40 pF is displayed as green, indicating that a bionic membrane with appropriate thickness is formed; a capacitance value lower than 15 pF or higher than 40 pF is displayed as red, indicating that an unqualified membrane is formed.
[0094] The membrane capacitance value of the amphiphilic block copolymer formed into a biomimetic membrane on a nanopore sequencing chip is generally 15-40 pF. The test results of the different polylactic acid triblock copolymers synthesized by the present invention formed into a biomimetic membrane on a nanopore sequencing chip are shown in Table 2 below.
[0095] Table 2 The results show that the different polylactic acid triblock copolymers synthesized by the present invention can self-assemble into biomimetic membranes on the micropores of the nanopore sequencing chip, and the membrane capacitance of the biomimetic membrane is 15-40 pF. Compared with the phospholipid membrane, the biomimetic membrane is thicker. Among them, the film-forming rate of the polylactic acid triblock copolymer with a degree of polymerization of 13 for the hydrophobic block PLA can be maintained at a high level of 75%-80%. Among all the synthesized polylactic acid triblock copolymers, the polylactic acid triblock copolymer with a degree of polymerization of 13 for the hydrophobic block PLA and a degree of polymerization of 4 for the hydrophilic block PMOXA has a better film-forming effect.
[0096] The electrical characterization of membrane capacitance of different polylactic acid triblock copolymers synthesized in the present invention into biomimetic membranes on nanopore sequencing chips is shown in Figure 4 (HO-PMOXA4-PLA 13 -PMOXA4-OH)、 Figure 5 (MA-PMOXA4-PLA 13 -PMOXA4-MA), Figure 6 (HO-PMOXA2-PLA 13 -PMOXA2-OH).
[0097] This example also tests the number of films and the film-forming rate of other polylactic acid triblock copolymers. The results are shown in Table 3.
[0098] Table 3 The above results show that the degree of polymerization, number average molecular weight and total degree of polymerization ratio of the hydrophilic block of the polylactic acid triblock copolymer have a great influence on the film-forming effect of the biomimetic membrane. First, the mechanical properties of the polylactic acid triblock copolymer with a number average molecular weight lower than 2000 g / mol are poor, and the biomimetic membrane formed on the chip is prone to leakage or almost no biomimetic membrane is formed. The polylactic acid triblock copolymer with a number average molecular weight higher than 6000 g / mol is prone to blockage when forming a biomimetic membrane on the chip, showing almost no biomimetic membrane formation. The film-forming rates of these polylactic acid triblock copolymers on the nanopore sequencing chip are all lower than 10%, and they cannot enter the subsequent embedding of nanopore proteins and sequencing links. For polylactic acid triblock copolymers whose total degree of polymerization of the hydrophilic block is not in the range of 20%-40%, even if they can form bionic membranes, there is a problem that the core hydrophobic block region does not match the nanopore protein (i.e., the membrane pore matching degree is low). When the nanopore protein is embedded, the bionic membrane is easily squeezed and deformed or the membrane ruptures, and thus the nanopore protein cannot be embedded.
[0099] In summary, the test example found that by controlling the number average molecular weight of the polylactic acid triblock copolymer to 2000-6000 g / mol and the total degree of polymerization of the hydrophilic block to 20%-40%, the size of the core hydrophobic block region can be better guaranteed, so that the thickness of the formed bionic membrane can be controlled to an appropriate thickness (e.g., 6-10 nm), thereby ensuring that the formed bionic membrane has excellent mechanical properties and thermal stability, will not degrade under normal environmental conditions, and has good biocompatibility, and is particularly suitable for forming bionic membranes based on nanopore sequencing chips, embedding nanopore proteins and sequencing, etc.
[0100] Test Example 2 Comparative test of the stability of biomimetic membranes and phospholipid membranes formed on nanopore sequencing chips In this example, phospholipids, commonly used polysiloxane copolymer PMOXA-PDMS-PMOXA (i.e., HO-PMOXA6-PDMS 27 -PMOXA6-OH) and the polylactic acid triblock copolymer PMOXA-PLA-PMOXA (i.e., HO-PMOXA4-PLA 13 -PMOXA4-OH) was tested for stability on a nanopore sequencing chip. The film forming method was the same as in Test Example 1.
[0101] The stability test results on day 1, day 15, day 30 and day 60 are shown in Table 4 below.
[0102] Table 4 The above experimental results show that the polylactic acid triblock copolymer synthesized by the present invention is higher than conventional polysiloxane copolymers in film forming rate, and can be substantially equal to the phospholipid membrane with generally recognized good film forming performance. However, along with the increase of the standing time, the film falling rate of the phospholipid membrane is more and more higher, and when the 60th day, the film falling rate is close to 50%. The polylactic acid triblock copolymer synthesized by the present invention not only has a high film forming rate on the 1st day, and even if the standing time increases, the film falling rate of the biomimetic membrane formed is very low, and can even be controlled at 2.5%, which is higher than the biomimetic membrane formed by the polysiloxane copolymer with generally recognized good stability.
[0103] In summary, the polylactic acid triblock copolymer synthesized in the present invention has high film forming rate and film quality, good uniformity and stability of the biomimetic film, and extremely low film drop rate. The film stability time of the polylactic acid triblock copolymer synthesized in the present invention can be maintained at about 60 days (compared with the membrane stability time of the phospholipid membrane of about 30 days), and after 60 days of film formation, it can still maintain a state suitable for nanopore protein embedding.
[0104] Polylactic acid triblock copolymer (HO-PMOXA4-PLA 13 -PMOXA4-OH) and polysiloxane copolymer (HO-PMOXA6-PDMS 27 The electrical characterization of the membrane capacitance of the biomimetic membrane formed by the nanopore sequencing chip was shown in Figure 60. Figure 7 and Figure 8 .
[0105] Test Example 3 Nanopore protein embedding behind biomimetic membrane or phospholipid membrane formed on nanopore sequencing chip After the formed biomimetic membrane is stable, add 0.5-2.0 μL of a biological protein (such as a-Hemolysin or MspA or CsgG) solution diluted 1-2 million times with a buffer. The concentration of the biological protein solution before dilution is 1-2 mg / mL. After applying an embedding voltage at both ends of the biomimetic membrane, nanopore proteins can be embedded in the biomimetic membrane.
[0106] In this example, phospholipids, commonly used polysiloxane copolymer PMOXA-PDMS-PMOXA (i.e., HO-PMOXA6-PDMS 27 -PMOXA6-OH) and the polylactic acid triblock copolymer PMOXA-PLA-PMOXA (i.e., HO-PMOXA4-PLA 13 -PMOXA4-OH) was tested on a nanopore sequencing chip (256 micropores). The total volume of the added biological protein MspA solution, the embedding voltage and the nanopore stabilization time are shown in Table 5 below.
[0107] Table 5 The above results show that the polylactic acid triblock copolymer synthesized in the present invention has an embedding performance close to that of a phospholipid membrane after being applied to a nanopore sequencing chip, and requires a smaller volume of biological protein and a lower embedding voltage than a biomimetic membrane formed by a polysiloxane copolymer. In other words, compared with the biomimetic membrane formed by a polysiloxane copolymer, the polylactic acid triblock copolymer synthesized in the present invention has excellent bioaffinity, membrane pore matching, and easily achievable embedding conditions, and requires low voltage stimulation and low protein amount for embedding, which not only saves experimental costs, but also avoids, to a certain extent, the problems of instability of the conformation of nanopore proteins or membrane rupture caused by the stimulation of a higher embedding voltage.
[0108] The results of embedding MspA nanopores in the biomimetic membrane formed by polylactic acid triblock copolymer, such as Fig. 9 , Fig.10 , Fig.11 (horizontally: test time, unit: ms, vertically: current value, unit: pA; CNN: location of the micropore structure of the nanopore sequencing chip). The above results show that after the MspA nanopore is embedded, the membrane state of the biomimetic membrane has slight fluctuations and tends to be stable overall. The embedded MspA nanopore protein includes a single pore (opening current is less than 400pA, Fig. 9 ) and porous (opening current is 400pA-600pA, Fig.10 ). Fig.11 The membrane current signal after embedding MspA nanopores is shown. After multiple membrane capacitance and embedding tests, MspA nanopores can stably exist on the biomimetic membrane formed by polylactic acid triblock copolymer for more than 60-90 days.
[0109] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. An amphiphilic triblock copolymer, characterized in that: The amphiphilic triblock copolymer has a hydrophilic block A-hydrophobic block B-hydrophilic block A structure, wherein the structural unit of the hydrophilic block A includes poly(2-methyloxazoline), the structural unit of the hydrophobic block B includes poly(lactic acid), the degree of polymerization of the hydrophilic block A is n, the degree of polymerization of the hydrophobic block B is m, and m+n≤25; the ratio of the total degree of polymerization of the hydrophilic block A to the total degree of polymerization of the amphiphilic triblock copolymer includes 20%-40%, and the number average molecular weight of the amphiphilic triblock copolymer includes 2000-6000 g / mol.
2. The amphiphilic triblock copolymer according to claim 1, characterized in that The amphiphilic triblock copolymer is HO-PMOXA n -PLA m -PMOXA n -OH, where m and n represent the degree of polymerization.
3. The amphiphilic triblock copolymer according to claim 1, characterized in that n / m includes 1:3-8.
4. The amphiphilic triblock copolymer according to claim 1, characterized in that The amphiphilic triblock copolymer is MA-PMOXA n -PLA m -PMOXA n -MA, where m and n represent the degree of polymerization.
5. Use of the amphiphilic triblock copolymer according to any one of claims 1 to 4 in the preparation of a biomimetic membrane.
6. The use according to claim 5, characterized in that The biomimetic membrane is used for embedding nanoporous proteins.
7. The use according to claim 6, characterized in that The embedding method comprises adding a nanoporous protein solution to the bionic membrane and then applying an embedding voltage to achieve the embedding of the nanoporous protein.
8. The use according to claim 7, characterized in that The final concentration of the nanoporous protein solution at the biomimetic membrane of a single microporous structure is 1-2×10 -6 mg / mL.
9. A method for preparing a biomimetic membrane on a nanopore sequencing chip, comprising the following steps: S301 preparing an amphiphilic triblock copolymer solution; S302 preparing a polar solution; S303 adding the polar solution to the pretreated nanopore sequencing chip; S304 After adding the amphiphilic triblock copolymer solution to the microporous structure of the nanopore sequencing chip, the polar solution is added, and the amphiphilic triblock copolymer self-assembles into the bionic membrane at the microporous structure; in, The amphiphilic triblock copolymer is the amphiphilic triblock copolymer according to any one of claims 1 to 4.
10. The method according to claim 9, characterized in that The nanopore sequencing chip has ≥2 micropore structures, and the final concentration of the nanopore protein solution at the biomimetic membrane of a single micropore structure is 1-2×10 -6 mg / mL.
Citation Information
Patent Citations
Phospholipid / polymer bionic composite-formula membrane as well as preparation method therefor and use thereof
WO2023123434A1